The complete chloroplast genome and phylogenetic analysis of Corydalis fangshanensis W.T. Wang ex S.Y. He (Papaveraceae) - Zhiying Yu; Tianhua Zhou; Niya Li; Dong Wang (Mitochondrial DNA. Part B. Resources, 2021)
The complete chloroplast (cp) genome of Corydalis fangshanensis W.T. Wang ex S.Y. He, a Chinese endemic plant with limestone-specific distribution was first reported. The cp genome was circular in structure and 192,554 bp in length, consisting of a large single copy region (LSC, 98,393 bp), two inverted repeat regions (IRs, 42,263 bp), and a small single copy region (SSC, 9,635 bp). The overall GC content of the genome was 40.26%. It encoded 112 unique genes, including 78 protein-coding genes, 30 tRNA genes, and 4 rRNA genes. Phylogenetic analysis resolved C. fangshanensis was closely related to C. saxicola G.S. Bunting within Corydalis sect. Thalictrifoliae (Fedde) Lidén, in line with morphological character-based taxonomy. Our result provides informative data for studying the taxonomy, phylogeny and ecology of Corydalis, especially species with specific-limestone distribution and also for studying the adaptive evolution in plants.